A Monetary Policy for Employment in the WAEMU - Moustaphaly, Mouhamadou (DEMO, 2020)
Despite great results of member countries of the West African Monetary and Economic Union (WAEMU) in the attainment of the convergence conditions the issues of poverty incidence and employment remain important in the eight economies. The renewed debate on macroeconomic linkages in the aftermath of the 2008 global crisis, leads us to wonder whether there would not be a room to improve significantly the effectiveness of current economic policies in developing economies especially those in the WAEMU. Indeed unemployment remains high even if inflation is duly under control and growth has reached unprecedented levels in the Union. The main message of this paper is that targeting inflation solely is not sufficient to promote economic and social development. The Central Bank of West African States (BCEAO) may recourse to (in) direct instruments (reserve requirement or even quantitative objectives for banks in terms of credit to SMEs) to induces the right incentives for the financial system to finance more directly small business and other SMEs that create jobs.(original abstract)
Keywords: Monetary policy; Unemployment; Monetary unions